Language proficiency and labour market performance of immigrants in the UK - Dustmann, Christian [Verfasser]; Fabbri, Francesca [Verfasser] (My University, 2000)
"
Keywords: P 1.5 Migranten; G 1.2.3.1 Potenziale; I 2.2.1 Westeuropa; Ausländer; Sprachkenntnisse; Arbeitsmarktchance; Quantitative Angaben; Großbritannien